2000
DOI: 10.1016/s0092-8674(00)00093-3
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophosmin/B23 Is a Target of CDK2/Cyclin E in Centrosome Duplication

Abstract: In animal cells, duplication of centrosomes and DNA is coordinated. Since CDK2/cyclin E triggers initiation of both events, activation of CDK2/cyclin E is thought to link these two events. We identified nucleophosmin (NPM/B23) as a substrate of CDK2/cyclin E in centrosome duplication. NPM/B23 associates specifically with unduplicated centrosomes, and NPM/B23 dissociates from centrosomes by CDK2/cyclin E-mediated phosphorylation. An anti-NPM/B23 antibody, which blocks this phosphorylation, suppresses the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
562
2
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 617 publications
(599 citation statements)
references
References 30 publications
29
562
2
6
Order By: Relevance
“…Previous reports have shown that NPM is involved in the assembly and/or intranuclear transport of pre-ribosomal particles and in cytoplasmic/nuclear trafficking (Spector et al, 1984;Yung et al, 1985;Borer et al, 1989). In mitotic cells, most nuclear proteins were dispersed throughout the cytoplasm, including NPM, which then re-localised to the centrosomes, and later to each daughter cell that received one centrosome bound by NPM after mitosis (Okuda et al, 2000). Interestingly, we also found that some of the non-mitotic cells, such as adult cerebral neuronal cells, epithelial cells of the adult kidney proximal tubule, and embryo osteoblast and thymic cells contain cytoplasmic NPM.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous reports have shown that NPM is involved in the assembly and/or intranuclear transport of pre-ribosomal particles and in cytoplasmic/nuclear trafficking (Spector et al, 1984;Yung et al, 1985;Borer et al, 1989). In mitotic cells, most nuclear proteins were dispersed throughout the cytoplasm, including NPM, which then re-localised to the centrosomes, and later to each daughter cell that received one centrosome bound by NPM after mitosis (Okuda et al, 2000). Interestingly, we also found that some of the non-mitotic cells, such as adult cerebral neuronal cells, epithelial cells of the adult kidney proximal tubule, and embryo osteoblast and thymic cells contain cytoplasmic NPM.…”
Section: Discussionmentioning
confidence: 98%
“…Earlier studies have shown that the level of NPM is markedly and promptly increased in association with cell commitment to mitogenesis (Feuerstein and Mond, 1987;Feuerstein et al, 1988). It has also been shown that NPM is a direct target of the Myc transcription factor during ribosomal biogenesis (Zeller et al, 2001) and cyclin E/CDK2 kinase activity during centrosome duplication (Okuda et al, 2000). Nucleophosmin physically interacts with several other cellular factors such as the retinoblastoma susceptibility gene product pRB (Takemura et al, 1994(Takemura et al, , 1999, the cell cycle G2 -M checkpoint factor Gadd45a (Gao et al, 2005), and the tumour suppressor p14 ARF (Itahana et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This protein is mainly localized in granular regions of the nucleolus and is associated with ribosome biogenesis. It also plays a substantial role in cell-cycle progression and cell division [26][27][28]. NPM/B23 binds to retinoblastoma protein (pRb) and synergistically stimulates DNA polymerase-α [26].…”
Section: Role Of Npm In Pbrmentioning
confidence: 99%
“…Down-regulation of NPM/B23 mRNA delays the entry of cells into mitosis [27]. Unduplicated centrosomes have been found to bear NPM/B23, phosphorylation of which by CDK2-cyclin E appears to be required for the initiation of centrosome duplication during mitosis [28,29]. The fact that NPM/B23 shuttles between nucleoli and cytoplasm suggests that its function is not restricted within the nucleolus [30].…”
Section: Role Of Npm In Pbrmentioning
confidence: 99%